Keberkesanan bahan bantu mengajar dalam pembelajaran bahasa Arab j-QAF / Norshida Hashim - Norshida, Hashim (2012)

(untitled)
The research aims to investigate the effectiveness of teaching aids in Arabic Language learning among Standard 5 j-QAF program students. 60 students from Sekolah Kebangsaan Taman Klang Jaya, Klang, Selangor are chosen as this research respondents. The findings shows that 3 most favorable teaching aids are computer (90.0%), pictures (76.7%) and power point slides (75.0%). The questionnaire given using SPSS version 12.0 software to find out the frequency and percentage. Based the questionnaire also shown that the relations between these factors; students perception towards Arabic Language, students perception towards teaching aids and students perception towards teaching and learning practices in Arabic Language. To identify the effectiveness of teaching aids, the respondents are divided randomly into 2 groups namely control group and experiment group using the design of Quasi-experiment method. Post test had been on both groups. The experiment group had gone through teaching and learning with teaching aids, while the control group faced teaching and learning as usual. The data are analyzed using SPSS Version 12.0 software to find out the min score and the t- value. The findings shows that there are differences in the min score of the group with no exposure to teaching aids that is the min score of the experiment group (71.97) bigger than the min score of the control group (55.47) and there is significant p<.05 between the usage of teaching aids with the achievement of students. This shows that the usage of teaching aids are able to improve the learning achievement among students. The finding from the interview of the teacher involved shows that the factor as well as time consuming, financial factor, burden from other responsibility and the lack of support from all, had been the main problems in providing teaching aids.